20th Anniversary Conference of the Journal Avances en Supervisión Educativa.Conclusions of Discussion Panel 2: School Autonomy and the Role of the Educational Inspectorate - Cuadrado Muñoz, Francisco; Lozano García, Alejandro (Avances en Supervisión Educativa, 2026)
This text outlines the approach and conclusions of a focus group held during the 20th-anniversary conference of Avances en Supervisión Educativa (Madrid, November 2025), which focused on the autonomy of educational institutions and the role of the Education Inspectorate. It explains how the working group was structured using the focus group methodology, beginning with a review of the current state of the art on the subject and the participants’ views gathered through a brief open-ended questionnaire. All the information derived from both the discussion group and the questionnaire responses has been analysed qualitatively, cross-referencing the two sources. Finally, the main conclusions of the entire process are presented regarding the possibilities for school autonomy and the role played by the Education Inspectorate.
Keywords: School autonomy; Education Inspectorate; advisory support; evaluation; accountability; qualitative methodologies